2015
DOI: 10.1159/000366007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tamsulosin 0.2 mg for Symptomatic Bladder Outlet Obstruction Secondary to Benign Prostatic Enlargement: Data from a Korean Multicenter Cross-Sectional Study

Abstract: Aims: To estimate efficacy and treatment satisfaction with tamsulosin 0.2 mg in patients with symptomatic bladder outlet obstruction secondary to benign prostatic enlargement and lower urinary tract symptoms in relation to personal satisfaction. Methods: The study was conducted in 1,260 subjects who were asked to fill in detailed questionnaires designed to evaluate their satisfaction with the treatment and symptom improvement 8 weeks after receiving tamsulosin 0.2 mg. Results: After being treated with tamsulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In Korea, tamsulosin 0.4 mg has only recently been approved for use in patients with BPH and there has since been an increase in the use of combination therapy that includes this dose [25,26]. Continued increase in the use of the combination of dutasteride 0.5 mg and tamsulosin 0.4 mg is expected, particularly given the low satisfactory relief of symptoms observed in patients using tamsulosin 0.2 mg [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, tamsulosin 0.4 mg has only recently been approved for use in patients with BPH and there has since been an increase in the use of combination therapy that includes this dose [25,26]. Continued increase in the use of the combination of dutasteride 0.5 mg and tamsulosin 0.4 mg is expected, particularly given the low satisfactory relief of symptoms observed in patients using tamsulosin 0.2 mg [27].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, tamsulosin 0.4 mg has only recently been approved for use in patients with BPH and there has since been an increase in the use of combination therapy that includes this dose [ 29 , 30 ]. Continued increase in the use of the combination of dutasteride 0.5 mg and tamsulosin 0.4 mg is expected, particularly given the low satisfactory relief of symptoms observed in patients using tamsulosin 0.2 mg [ 31 ]. However, studies have shown inferior medication compliance with free- versus fixed-dose combination therapy [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Korea demonstrated that 35.5% of BPH patients were not satisfied after treatment with Tam 0.2 [22]. The reason for dissatisfaction was low efficacy and side effects.…”
Section: Discussionmentioning
confidence: 99%